Dakwah Inklusif bagi Penyintas Trauma: Perspektif Komunikasi Empatik - Samaual (Penerbit Cahaya Kata, 2026)
This research explores the reconstruction of dawah narratives that are supportive of trauma survivors through the lens of empathetic communication. Traditionally, dawah narratives have often been confined to normative, textual approaches that sometimes trigger stigmatization or spiritual bypassing for individuals experiencing profound trauma. Using a descriptive qualitative method with a literature review, this study formulates an inclusive dawah model that prioritizes emotional validation and safe spaces. The results indicate that empathetic communication in dawah is not merely rhetoric but involves active listening techniques and the use of non-judgmental diction. Inclusive dawah for trauma survivors must integrate the values of compassion (rahmah) with the principles of trauma psychology so that religious messages can serve as a means of healing (shifa) rather than an additional burden.